THU0150 Impact of comorbidity burden and obesity on the effectiveness of tocilizumab in patients with rheumatoid arthritis. (12th June 2018) - Pappas, D.; Etzel, C.; Crabtree, M.; Best, J.; Zlotnick, S.; Kremer, J.
Abstract : Background: Few real-world studies have evaluated the impact of comorbidity burden or obesity on the effectiveness of tocilizumab (TCZ) for the improvement of rheumatoid arthritis (RA) disease activity. Objectives: To compare the effectiveness of TCZ in treating RA in patients with high vs low comorbidity burden and in obese vs nonobese patients in US clinical practice. Methods: Patients in the Corrona RA registry who initiated TCZ and had follow-up visits at 6 and 12 months after initiation were included. To assess the impact of comorbidity burden on TCZ effectiveness, outcomes were stratified by patients with low Charlson Comorbidity Index (CCI=1) vs high (CCI ≥2). To assess the impact of obesity, outcomes were stratified by patients with BMI <30 (nonobese) vs ≥30 (obese). The primary outcome was mean change in CDAI at 6 and 12 months. Secondary outcomes were mean change in HAQ, the proportions of patients with change ≥the minimum clinically important difference (MCID) in CDAI and HAQ and the proportion who achieved low disease activity (LDA; CDAI≤10). Baseline demographics, clinical characteristics, disease activity and treatment history in the comorbidity and BMI cohorts were compared separately using standardised differences; characteristics with |standardised difference|>0.1 were identified as covariates for inclusion in adjusted comparisons. Outcomes were compared between cohorts using two-sample t -tests or χ 2 tests in unadjusted analyses and linear or logistic regression models to adjust for covariates. Results: Of 770 patients who initiated TCZ and had CCI data available at baseline (93.8% treated with intravenous [IV] TCZ and 6.2% with subcutaneous [SC] TCZ), 575 (74.7%) had a low CCI and 195 (25.3%) a high CCI. Patients with a high CCI were older (mean [SD] age, 61.5 [12.3] vs 56.9 [13.1] years), were more likely to be obese (52.8% vs 41.7%), had a longer disease duration (mean [SD], 12.8 [9.9] vs 11.6 [8.9] years) and had higher mean (SD) baseline CDAI (25.7 [13.4] vs 23.9 [13.9]) and HAQ (0.71 [0.57] vs 0.57 [0.51]) scores than those with a low CCI. Of the 805 TCZ initiators with BMI data available at baseline (93.9% treated with IV TCZ and 6.1% with SC TCZ), 449 (55.8%) were not obese and 356 (44.2%) were obese. Obese patients were younger (56.7 [12.0] vs 59.0 [13.7] years), had shorter disease duration (11.4 [8.6] vs 12.6 [9.7] years) and had higher baseline CDAI (25.4 [14.3] vs 23.6 [13.4]) and HAQ (0.65 [0.53] vs 0.57 [0.53]) scores than nonobese patients. Patients in all cohorts had improvement from baseline in CDAI at 6 and 12 months, with no significant differences between those with a low vs high CCI or between obese vs nonobese patients (table 1). Secondary outcomes yielded similar results (table 1). Conclusions: In this real-world analysis, the effectiveness of TCZ for the improvement of RA disease activity was comparable among patients regardless of comorbidity burden or obesity. Acknowledgements: This study is sponsored by Corrona, LLC. Corrona has been supported through contracted subscriptions in the last 2 years by AbbVie, Amgen, Boehringer Ingelheim, BMS, Celgene, Crescendo, Eli Lilly, Genentech, Gilead, GSK, Horizon Pharma USA, Janssen, Merck, Momenta Pharmaceuticals, Novartis, Pfizer Inc., Roche, UCB and Valeant. Disclosure of Interest: D. Pappas Grant/research support from: Abbvie, Consultant for: Abbvie, Employee of: Corrona, LLC, C. Etzel Shareholder of: Corrona, LLC, Consultant for: Merck, Employee of: Corrona, LLC, M. Crabtree Employee of: Corrona, LLC, J. Best Shareholder of: Genentech, Inc., Employee of: Genentech, Inc, S. Zlotnick Shareholder of: Genentech, Inc., Employee of: Genentech, Inc, J. Kremer Shareholder of: Corrona, LLC, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly and Company, Genentech, GlaxoSmithKline, Pfizer, Regeneron, Sanofi